Characterization of the Importin-β binding domain in nuclear import receptor KPNA7. Issue 21 (15th November 2019) - Oostdyk, Luke T.; McConnell, Michael J.; Paschal, Bryce M.
Abstract : The KPNA family of mammalian nuclear import receptors are encoded by seven genes that generate isoforms with 42–86% identity. KPNA isoforms have the same protein architecture and share the functional property of nuclear localization signal (NLS) recognition, however, the tissue and developmental expression patterns of these receptors raise the question of whether subtle differences in KPNA isoforms might be important in specific biological contexts. Here, we show that KPNA7, an isoform with expression mostly limited to early development, can bind Importin-β (Imp-β) in the absence of NLS cargo. This result contrasts with Imp-β interactions with other KPNA family members, where affinity is regulated by NLS cargo as part of a cooperative binding mechanism. The Imp-β binding (IBB) domain, which is highly conserved in all KPNA family members, generally serves to occlude the NLS binding groove and maintain the receptor in an auto-inhibited 'closed' state prior to NLS contact. Cooperative binding of NLS cargo and Imp-β to KPNA results in an 'open'state. Characterization of KPNA2–KPNA7 chimeric proteins suggests that features of both the IBB domain and the core structure of the receptor contribute to the extent of IBB domain accessibility for Imp-β binding, which likely reflects an 'open' state. We also provide evidence that KPNA7 maintains an open-state in the nucleus. We speculate that KPNA7 could function within the nucleus by interacting with NLS-containing proteins.